Australian metal music : identities, scenes, and cultures - Hoad, Catherine (Emerald studies in metal music and culture., 2019)
Defining 'Australian metal' is a challenge for scene members and researchers alike. Australian metal has long been situated in a complex relationship between local and global trends, where the geographic distance between Australia and metal music's seemingly traditional centres in the United States and United Kingdom have meant that metal in Australia has been isolated from international scenes. While numerous metal scenes exist throughout the country, 'Australian metal' itself, as a style, as a sound, and as a signifier, is a term which cannot be easily defined. This book considers the multiple ways in which 'Australianness' has been experienced, imagined, and contested throughout historical periods, within particular subgenres, and across localised metal scenes. In doing so, the collection not only explores what can be meant by Australian metal, but what can be meant by 'Australian' more generally. With chapters from researchers and practitioners across Australia, each chapter maps the distinct ways in which 'Australianness' has been grappled with in the identities, scenes, and cultures of heavy metal in the country. Authors address the question of whether there is anything particularly 'Australian' about Australian metal music, finding that often the 'Australianness' of Australian metal is articulated through wider, mythologised archetypes of national identity. However, this collection also reveals how Australianness can manifest in metal in ways that can challenge stereotypical imaginings of national identity, and assert new modes of being metal 'downungerground'.